Pemikiran Politik Islam di Indonesia: Menggali Dimensi Substantif dalam Wacana Formalistik - Rachmat Panca Putera (Protasis: Jurnal Bahasa, Sastra, Budaya, dan Pengajarannya, 2024)
This study aims to examine the shift in Islamic political thought in Indonesia, from a formalistic approach to a substantive one, as well as the factors that drive this change. The formalistic approach, which emphasizes symbols and the rigid application of Islamic law in the state structure, is increasingly seen as irrelevant to the social-political dynamics of plural Indonesia. In contrast, the substantive approach, which focuses on achieving the social goals of Islam, such as justice and welfare, is considered more adaptable to the needs of modern society. This research uses a qualitative method with a literature review approach, analyzing various relevant sources to identify the paradigm shift in Islamic political thought. The findings indicate that this shift is largely influenced by social developments and political challenges faced by Indonesian society. The implications of these findings highlight the importance of adopting a substantive approach in formulating inclusive public policies that can strengthen social harmony in Indonesia. This approach also offers a new foundation for the development of Islamic political thought that is more relevant to the challenges of the times.